2016
DOI: 10.1016/j.drugalcdep.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent effects of cannabis-induced analgesia

Abstract: Background Preclinical studies demonstrate that cannabinoid-mediated antinociceptive effects vary according to sex; it is unknown if these findings extend to humans. Methods This retrospective analysis compared the analgesic, subjective and physiological effects of active cannabis (3.56 - 5.60% THC) and inactive cannabis (0.00% THC) in male (N = 21) and female (N = 21) cannabis smokers under double-blind, placebo-controlled conditions. Pain response was measured using the Cold-Pressor Test (CPT). Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 68 publications
2
57
3
Order By: Relevance
“…In humans, cannabis exposure increases heart rate in both women and men [45, 46], but to a lesser extent in women [4648]. Women have reported greater sedative effects [46] and dizziness [49] compared to men in response to cannabis, though amount of cannabis per body weight was not adjusted.…”
Section: Sex Differences In the Endocannabinoid Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, cannabis exposure increases heart rate in both women and men [45, 46], but to a lesser extent in women [4648]. Women have reported greater sedative effects [46] and dizziness [49] compared to men in response to cannabis, though amount of cannabis per body weight was not adjusted.…”
Section: Sex Differences In the Endocannabinoid Systemmentioning
confidence: 99%
“…Conflicting evidence may be due to smoking status differences in the populations of each study, as well as differences in THC capsule dosing indicated in each experimental design. Cannabis-induced increases in “good” and “take again” ratings were shown to be enhanced in women compared to men [11], but also shown to be gender-independent [48]. In a female-only study, cannabis exposure increased ratings of confusion among regular and intermittent cannabis users, although this effect was stronger among intermittent users [45].…”
Section: Sex Differences In the Rewarding Properties Of Cannabinoidsmentioning
confidence: 99%
“…There are known sex differences in pain perception and neuroimmune responses (Sorge & Totsch, ), as well as sex‐dependent cannabinoid‐mediated effects (Cooper & Craft, ; Craft, Marusich, & Wiley, ). Therefore, potential sexual dimorphisms that may underlie the treatment efficacy of different cannabinoids in the context of neuropathic pain need to be addressed (Cooper & Haney, ), especially as these agents are being clinically applied with mixed outcomes, which could be due to a patient's sex, as well as being influenced by gender roles. The aim of this investigation was to assess the early treatment efficacy of CBDA‐ME in a preclinical sciatic nerve cuff model of neuropathic pain (Mosconi & Kruger, ) in both males and females.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a number of human experimental acute pain studies, we excluded them for several reasons. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] First, there are significant differ-ences in trial design and patient population compared with clinical trials. As well, cannabinoid impact on experimental acute pain was recently explored as the primary topic of a well-done systematic review and meta-analysis.…”
Section: Study Eligibilitymentioning
confidence: 99%